CAN UNIVERSAL LINGUISTIC FUNDAMENTALS CONTRIBUTE TO THE INTERPRETATION OF EFL LEARNING? - Al-Khatib, Hayat (European Scientific Journal, ESJ, 2013)
A number of studies have argued that many EFL students face difficulties in learning English at various levels and with different skills (Arlington and Hewings, 2012; Seargeant, 2012a; Mayor, 2012; Seargeant and Swann, 2011). With the globalization of English and its spread to different contexts of use, new perspectives are emerging on communicative practices of the users and the multiple emerging patterns of errors (Seargeant 2012b; Mayor and Allington, 2012; Hewings and Tagg, 2012). Al-Mukattash (1983) examined inherent language difficulties impeding the learning of the target language. Hamdan and Amayreh (2007) underlined phonological and articulation problems for Jordanian learners. Kambal (1980) reported syntactic problems for Sudanese and Egyptian learners. Zoughoul and Taminian (1984) found serious lexical problems in EFL exchanges of Arab university students. Diab and Hamdan (1999) documented heavy reliance on dictionaries to aid the comprehension of meaning as well as articulation. Rabab’ah (1984) identified communicative obstacles in message transmission. This study is concerned with identifying the areas of difficulties that EFL learners from Arabic background face when learning English. The study traces correlation between proficiency and language performance in an attempt to examine whether universal linguistic fundamentals can contribute to the interpretation of language learning in foreign language contexts. The study is comprised of two stages. A pilot sample of 169 students was followed for a six month period in an intensive English programme to identify the weaknesses the learners experienced at three competency levels. In the second stage, a larger sample of 1011 students was studied for a period of one year, to determine the causes of the difficulties and explore whether universal linguistic fundamentals can contribute to EFL learning. Data include individual student records of progression and assessment, collected through through various set tasks and class performance. BERA ethical codes were applied in the research study in relation to participants’ awareness and consent. The findings identified three main areas where learners experience difficulties in learning English: areas that relate to the linguistic ambiguities of the target language; areas that relate to the prominence of features in the first language, and areas that relate to the competency levels of the learners. The study concludes with a set of propositions that can be developed to improve the Arab learners’ experience.